<u>Given:</u>
The two equations are
and ![5x-3y=11](https://tex.z-dn.net/?f=5x-3y%3D11)
We need to solve the equations using elimination method.
<u>Elimination method:</u>
Let us multiply the equation
by 5, we get;
---------(1)
Now, multiplying the equation
by -2, we get;
--------(2)
Adding equations (1) and (2), we have;
![\ \ \ 10x-25y=-35\\-10x+\ \ 6y=-22\\---------\\-19y=-57](https://tex.z-dn.net/?f=%5C%20%5C%20%5C%2010x-25y%3D-35%5C%5C-10x%2B%5C%20%5C%206y%3D-22%5C%5C---------%5C%5C-19y%3D-57)
![y=3](https://tex.z-dn.net/?f=y%3D3)
Thus, the value of y is 3.
Substituting
in the equation
, we have;
![2x-5(3)=-7](https://tex.z-dn.net/?f=2x-5%283%29%3D-7)
![2x-15=-7](https://tex.z-dn.net/?f=2x-15%3D-7)
![2x=8](https://tex.z-dn.net/?f=2x%3D8)
![x=4](https://tex.z-dn.net/?f=x%3D4)
Thus, the value of x is 4.
Hence, the solution of the system of equations is (4,3)
Therefore, Option A is the correct answer.